STUDI PENGALAMAN MAHASISWA DALAM MENERAPKAN SURFACE LEARNING DAN DEEP LEARNING MELALUI PENGGUNAAN AI DALAM PENULISAN AKADEMIK: Abstrak, pendahuluan, hasil & pembahasan, kesimpulan, daftar pustaka - Akila Ghaniya Salsabila Rahman; Lutfiah Nur Sakinah; Shafiyah Asy-Syifa Siregar; Anita Candra Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the use of Artificial Intelligence (AI) in students’ academic writing, identify learning tendencies, and analyze its implications for information management in the digital era. The research employs a descriptive qualitative approach, with data collected through open-ended questionnaires involving seven students from different academic backgrounds, supported by a literature review. The data were analyzed thematically to identify patterns of AI use, levels of student engagement, and the benefits and challenges encountered. The findings show that AI is mainly used in the early to middle stages of writing, including idea generation, outlining, paragraph development, and sentence refinement. Two main tendencies are identified: the use of AI as a supportive tool combined with independent verification and information processing, and the use of AI as an instant solution without deep analysis. Although AI improves efficiency and facilitates understanding, it also raises concerns regarding information validity, lack of source verification, and potential dependency that may weaken critical thinking skills. Therefore, the effectiveness of AI depends largely on users’ digital literacy. Critical awareness, selectivity, and academic integrity are essential to ensure that AI supports meaningful and reflective learning.